Wireless propagation studies in highly resonant and dynamic environments - Panitz, Mark (2011)
This thesis develops efficient tools for modelling wireless communications within highly resonant environments. The aim of these tools is to augment analysis of wireless systems inside closed metallic cavity environments. The primary application for these systems is within the aerospace industry where weight and space are restricted and robustness is critical. The use of ever-advancing wireless communication options would offer significant weight and cost savings and increase safety through supplementing or the replacement of wired systems. The use of a low power wireless system offers the greatest advantage in terms of flexibility and weight. Accordingly, the most suitable applications of the wireless systems are discussed in terms of existing avionic systems.